RUSSIA’S HIGH-GROWTH COMPANIES: TESTED THROUGH DEPRESSION - YURY ALEKSEEVICH Polunin; ANDREY YURJEVICH Yudanov (Мир новой экономики, 2018)
The search for the new growth factors of the Russian economy acquired special importance under the conditions of the today’s prolonged depression. According to international studies the high-growth companies (gazelles) act at the micro-economic level as the decisive factor of the growth of the GDP and employment. In the article is carried out the empirical estimation of the number of Russian population of gazelles and is examined thestylized life cycle of the high-growth firm. It is established that in the pre-crisis years the population of gazelles inthis country strongly exceeded the corresponding level of the developed countries. After 2008 gazelle’s population in Russia experienced a sharp reduction. Our study of the life cycle of the domestic of gazelles also confirmedtheir increased instability. The use of Birch index showed that in Russia the majority both the rapidly-growing and unsuccessfully developing firms are concentrated in one and the same branches (trade, building and other).Hypothesis is advanced, that the instability of the Russian gazelles is connected with the unfavorable business conditions in the goods producing sector of this economy.